(untitled) (Maritime Park: Journal of Maritime Technology and Society, 2022)
Corrosion is one of the most common causes of damage to mooring buoys due to oxidation on the surface of the steel plate. The purpose of this study was to determine the need and placement of cathodic protection as well as the costs required in procuring cathodic protection on moorings buoy using the rules of BKI (Indonesian Classification Bureau) and DNV (Det Norske Veritas Industry Norway). In the cathodic protection system there are two methods of cathodic protection, namely Sacrificial Anode Cathodic Protection (Sacrificial Anode) and Impressed Current Cathodic Protection (ICCP). In this study, the sacrificial anode method was used because the installation is simpler so it does not require special skills and the anode connector is cathodic protected. Mooring buoy with a height of m, a diameter of meters with a cathodic protection design life of 5 years. The anode used in this study is an anode with a Longated flush-mounted Z9.0H1 (Welded Type) with dimensions of 355 x 85 x 45 mm. From the results of this study, it was found that the total anode mass needed to protect the mooring buoy is 26.95 kg with the installation distance between the anodes on the topside hull plate is 34.557 m and the bottom swim hull plate is 47.123 m and the estimated cost required to provide mooring buoy is IDR 4,284,900.